Interdiscursive readings in cultural consumer research - Rossolatos, George (Cambridge Scholars Publishing, 2018)
The cultural consumption research landscape of the 21st century is marked by an increasing cross-disciplinary fermentation. At the same time, cultural theory and analysis have been marked by successive 'inter-' turns, most notably with regard to the Big Four: multimodality (or intermodality), interdiscursivity, transmediality (or intermediality), and intertextuality. This book offers an outline of interdiscursivity as an integrative platform for accommodating these notions. To this end, a call for a return to Foucault is issued via a critical engagement with the so-called practice-turn. This r.